OBSERVATIONS ON THE GROWTH OF METAPENAEUS DOBSONI (MIERS) IN THE POLYETHYLENE FILM-LINED PONDS AT CALICUT BEACH - Lazarus, S; Nandakumaran, K (Indian Journal of Fisheries, 2011)
The growth ol Metapenaeus dobsoni in the polyethylene film-lined ponds is studied and growth parameters estimated. In the first two months the prawn attained a size of about 64 mm and in the next five months it added only 14 mm to its size, reaching a size of 78 mm by seven months.